Is There Any Reason to Prefer Cord Blood Instead of Adult Donors for Hematopoietic Stem Cell Transplants? - Beksac, Meral (Frontiers in Medicine, 2016)
As cord blood (CB) enables rapid access and tolerance to HLA mismatches, number of unrelated cord blood transplants have reached 30 000. Such transplant activity has been the result of international accreditation programs maintaining highly qualified CBUs reaching more than 600 000 CBUs stored worldwide. Efforts to increase stem cell content or engraftment rate of the graft by ex vivo expansion, modulation by molecules such as fucose, Prostaglandin E2 derivative, complement, CD26 inhibitors or CXCR4/CXCL12 axis have been able to accelerate engraftment speed and rate. Furthermore introduction of reduced intensity conditioning protocols, better HLA matching and recognition of the importance of HLA-C have improved CBT success by decreasing Transplant Related Mortality (TRM). Cord blood progenitor/stem cell content has been compared with adult stem cells revealing higher long-term repopulating capacity compared to BM-MSC and less oncogenic potential than Induced Progenitor Stem Cells. This chapter summarizes the advantage and disadvantages of CB compared to adult stem cells within the context of stem cell biology and transplantation.